2021
DOI: 10.1111/petr.14155
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic macrosteatosis in the US pediatric deceased liver donor population

Abstract: Introduction:The pediatric obesity epidemic is associated with early development of hepatic macrosteatosis, a hallmark of non-alcoholic fatty LI disease, which is thought to be more rapidly progressive in children than adults. Macrosteatosis in adult allografts is associated with allograft loss, but this has not been examined in pediatric donors. Methods:We studied all pediatric potential whole LI donors (2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018) who had a LI biopsy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
(55 reference statements)
1
4
0
Order By: Relevance
“…When comparing outcomes of AL by each abnormal variable, we further found that AL with >5% macrosteatosis were no different in terms of overall graft survival compared to NL. Our results correspond with the evolving paradigm that livers with increased levels of macrosteatosis may still be suitable for pediatric transplants [10][11][12][13][14]. In our cohort, the presence of inflammation in donor liver biopsies led to a lower overall graft survival and was found in 90% of graft loss events.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…When comparing outcomes of AL by each abnormal variable, we further found that AL with >5% macrosteatosis were no different in terms of overall graft survival compared to NL. Our results correspond with the evolving paradigm that livers with increased levels of macrosteatosis may still be suitable for pediatric transplants [10][11][12][13][14]. In our cohort, the presence of inflammation in donor liver biopsies led to a lower overall graft survival and was found in 90% of graft loss events.…”
Section: Discussionsupporting
confidence: 87%
“…Historically, in pediatric liver transplantation, healthier grafts with lower levels of macrosteatosis are preferred. Recent studies have shown that obese donors or liver grafts with >5% macrosteatosis do not adversely impact the outcomes of pediatric transplant recipients, thus we chose 5% macrosteatosis as a threshold for our study [12,13]. Irie et al demonstrated that pediatric patients who received a living donor liver transplant with moderate-to-severe macrosteatosis also had no difference in patient survival and that the degree of macrosteatosis decreased over time [14].…”
Section: Discussionmentioning
confidence: 99%
“…Considering previous publications that reported a regulatory role of IL-6 and IL-10 on IL-1 ( 11 , 12 , 14 , 15 ), IL-1 was investigated as a possible mediator involved in signaling mechanism underpinning IL-6 and IL-10 beneficial effects. For this, hepatic levels of IL-1α and IL-1β in LT and BD surgical settings were first determined.…”
Section: Resultsmentioning
confidence: 99%
“…In consideration of the previous data that suggest that the effects resulting from NO could involve signaling mechanisms requiring interleukins ( 12 , 16 , 17 , 19 21 ), we evaluated whether endogenous NO affects IL-6, IL-10, and IL-1β in non-steatotic and steatotic grafts from DBDs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation